Grantchester. The complete sixth season [videorecording (DVD)] - Green, Robson; Brittney, Tom, 1990-; Peake-Jones, Tessa; Weaver, Al, 1981- (PBS Distribution, 2021)
The year is 1958: Rev. Will Davenport is at odds with his own ideals when Leonard Finch is caught up in a scandal. It will take all of Will's skill and empathy to navigate the choppy waters and help the ones he loves.